ETHOS, PATHOS, LOGOS DAN KOMUNIKASI PUBLIK: A SYSTEMATIC LITERATURE REVIEW - Meidy Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Aristotle's rhetorical theory is one of the oldest communication theories. Aristotle's rhetoric is concerned with 'argument', which seeks to persuade an audience especially in the context of public communication. This journal aims to see the trend of Aristotle's rhetorical studies, categorize them based on the concept of artistic proofs and based on the topic of study, as well as to develop (purify) based on the assumptions of classical rhetoric theory using the Systematic Literature Review (SLR) method. We found that rhetorical theory studies by Aristotles are dominated by political communication topics. This journal also found a decrease in the number of studies using Aristotle's rhetorical theory. We argue that the character of rhetorical theory, which is considered